Estrutura do pericarpo de Banisteriopsis C.B.Rob. e Diplopterys A.Juss. (Malpighiaceae): Novos dados suportando a segregação genérica - Souto, Letícia Silva [UNESP]; Oliveira, Denise Maria Trombert (FapUNIFESP (SciELO), 2012)
Molecular studies have indicated that some species of Banisteriopsis would be more appropriately placed in Diplopterys. Both of these genera are neotropical members of the Malpighiaceae, a family that is widely diverse in South America, especially in the Brazilian savanna (cerrado). Studies concerning the anatomy of the reproductive organs of Malpighiaceae from the cerrado are very rare. Thus, the present work describes the morphology, anatomy, and ontogeny of the pericarp of B. campestris, B. oxyclada, B. stellaris, and D. pubipetala, comparing them and identify- ing characteristics that could support the segregation of genera. The fruits of Banisteriopsis studied here demonstrate structures very similar among themselves, while D. pubipetala shows numerous differences. The fruits of all species are schizocarpic and formed by three samara with dorsal wings, while the fruits of D. pubipetala also have lateral winglets on the seed chamber. The mesocarp of the Banisteriopsis species has groups of thick and elongated cells, while these cells form a continuous band in D. pubipetala; the endocarp of D. pubipetala proliferates markedly, forming an aerenchyma layer not seen in Banisteriopsis. Besides the homogeneous structure of the pericarp of the Banisteriopsis species, all referred distinctive characteristics support the maintenance of D. pubipetala in a different genus.
Pericarp structure in Banisteriopsis C.B.Rob. and Diplopterys A.Juss. (Malpighiaceae): New data supporting generic segregation
Keywords: Banisteriopsis campestris; Banisteriopsis oxyclada; Banisteriopsis stellaris; Diplopterys pubipetala; Ontogeny